Neuregulin-1β Partially Improves Cardiac Function in Volume-Overload Heart Failure Through Regulation of Abnormal Calcium Handling - Wang, Xuehui; Zhuo, Xiaozhen; Gao, Jie; Liu, Huibing; Lin, Fei; Ma, Aiqun (Frontiers in Pharmacology, 2019)
Background: Neuregulin (NRG-1), an important stress-mediated paracrine growth factor, has a cardioprotective effect in failing heart. However, the underlying mechanism remains unclear. The effects of NRG-1β on Ca2+ handling in heart failure (HF) rats were examined. Methods and Results: Volume-overload HF was induced in rats by aortocaval fistula surgery, sham-operated rats (SO) received the same surgical intervention without the fistula. Half of HF rats were injected with NRG-1β (NRG, 10 μg/kg•d) via the tail vein for 7 days, whereas the other half of HF rats and SO rats were injected with the same dose of saline. The echocardiographic findings showed left ventricular dilatation, systolic and diastolic dysfunction, and QTc interval prolongation in HF rats. The NRG-1β treatment attenuated the ventricular remodeling and shortened the QTc interval. Patch clamp recordings showed ICa-L was significantly decreased in the HF group, and NRG-1β treatment attenuated the decreased ICa-L. No significant differences in the kinetic properties of ICa-L were observed. The expressions of Cav1.2 and SERCA2a were significantly decreased, but the expression of NCX1 was significantly increased in the HF group. NRG-1β treatment could partially prevent the decrease of Cav1.2 and SERCA2a, and the increase of NCX1 in HF rats. Conclusions: These results suggest that reversal of disrupted Ca2+ handling proteins could be a novel mechanism partially underlying NRG-1β-improved cardiac function during HF rats. Key Words Heart failure • Neuregulin-1β • L-type calcium channel • Calcium handling •SERCA2a